Generation of high-intensity aluminum-ion beams at low energy; Technical Physics; Vol. 63, iss. 10 - Ryabchikov A. I. Aleksandr Ilyich; Shevelev A. E. Aleksey Eduardovich; Ananin P. S. Petr Semenovich; Sivin D. O. Denis Olegovich (2018, 2018)
Title screen